2008
DOI: 10.1111/j.1532-950x.2008.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Trephination of the Equine Rostral Maxillary Sinus: Efficacy and Safety of Two Trephine Sites

Abstract: The rostral RMS trephine portal is more reliable than the caudal site for entering the RMS. Horses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…14 Variation in paranasal sinus morphology, particularly of the maxillary septum, both with age and between horses, 5,15 means that direct, single-portal approaches to the RMS like we performed cannot reliably provide consistent access to the RMS. 2,4 In agreement with other studies, 2,4 we found that the rostral RMS approach provides more reliable access to the RMS than does the caudal RMS approach. By using a trans-illumination technique to identify the position of the maxillary septum the accuracy of direct trephination of the RMS was greatly enhanced using the light-indicated RMS approach.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…14 Variation in paranasal sinus morphology, particularly of the maxillary septum, both with age and between horses, 5,15 means that direct, single-portal approaches to the RMS like we performed cannot reliably provide consistent access to the RMS. 2,4 In agreement with other studies, 2,4 we found that the rostral RMS approach provides more reliable access to the RMS than does the caudal RMS approach. By using a trans-illumination technique to identify the position of the maxillary septum the accuracy of direct trephination of the RMS was greatly enhanced using the light-indicated RMS approach.…”
Section: Discussionsupporting
confidence: 92%
“…The RMS accommodates the reserve crowns of the 3rd, 4th, and 5th cheek teeth (Triadan 08, 09, 10), 5 and thus a complication of direct trephination into the RMS is damage to the alveolar bone overlying the apices of these cheek teeth or damage to the underlying teeth. 4 In agreement with a recent study, 4 damage to the alveolar bone and the apices of the cheek teeth was most prevalent in horses o6 years of age with the rostral RMS approach. Others have suggested that the skull should be examined radiographically before trephining into the RMS to guide selection of a portal that avoids the maxillary septum and dental structures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Endoscopic examination of the RMS and VCS was usually possible following perforation of the VCB, without having to trephine directly into the RMS ‐ which is technically difficult in young horses and risks damaging the alveoli (Barakzai et al . 2008; Perkins et al .…”
Section: Discussionmentioning
confidence: 99%